Effects of groove shape on microstructure and properties of resistance spot welding joints in WC-10Co/B318 steel. (December 2021) - Wu, Chunyan; Guo, Zhongning; Liu, Guoyue; Li, Yuanbo; Chen, Lingyu
Abstract: In resistance spot welding, groove shape has an important influence on joint performance. The groove shapes designed in this study are applied to a bimetal band-saw blade, which has theoretical and application value. Three groove shapes (straight, arc, and V-shaped) are designed on the backing bracket to weld WC-10Co and B318 steel. The welding process is imaged using a high-speed camera, and the distribution and change of heat in the welding process are compared and analyzed. The shear force, interfacial microstructure, and fracture surface are analyzed by shear tests, scanning electron microscopy, and energy-dispersive X-ray spectroscopy, and the relationship among the heat distribution, interfacial microstructure, and shear force is investigated. The results show that the reaction duration and temperature distribution at various interfacial positions of the different groove shapes are heterogenous, leading to an uneven interfacial reaction. For short welding time, the straight joint with heat concentrated in the center of the interface has larger deformation and so larger shear force. For long welding time, the reaction layer forms at the interface. At the straight joint interface, the η phase is distributed more and aggregates, thereby decreasing the shear force. At the other two joint interfaces, the distribution is more eutectic and the η phase is relatively dispersed, so the shear force is higher. The maximum shear forces of the joints are 1068.2 N (straight), 1138.1 N (arc), and 1231.7 N (V-shaped). For short welding time, the metallurgical reaction of the interface is insufficient, and the joint fractures at the interface. For long welding time, the fracture usually starts from the cracks on the WC-Co side, then propagates to the interfacial reaction layer, and finally fractures at the steel side. The appearance of cracks, reaction layer, extrusion, and inclusions reduces the shear force of the joint. Highlights: Reaction duration and temperature distribution were heterogenous at different groove shapes. The welding process, microstructure, and fracture morphology of the joints under various groove shapes were identified. The relationship among heat distribution, reactants, and joint strength were discussed.